2010
DOI: 10.1242/jcs.064352
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis root K+-efflux conductance activated by hydroxyl radicals: single-channel properties, genetic basis and involvement in stress-induced cell death

Abstract: SummaryReactive oxygen species (ROS) are central to plant stress response, signalling, development and a multitude of other processes. In this study, the plasma-membrane hydroxyl radical (HR)-activated K + channel responsible for K + efflux from root cells during stress accompanied by ROS generation is characterised. The channel showed 16-pS unitary conductance and was sensitive to Ca 2+ , tetraethylammonium, Ba 2+ , Cs + and free-radical scavengers. The channel was not found in the gork1-1 mutant, which lacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
384
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 449 publications
(411 citation statements)
references
References 88 publications
(131 reference statements)
13
384
0
14
Order By: Relevance
“…Plant GLRs were confirmed recently to be NSCC (Price et al, 2012;Forde, 2014). Therefore, activated by Glu, GLR may mediate stress-induced Ca 2+ uptake, with a consequent rise in cytosolic Ca 2+ , that in turn can activate the plasma membrane NADPH oxidase (Lecourieux et al, 2002), leading to elevated H 2 O 2 levels and a consequent formation of OH $ (as discussed above), leading to a massive K + efflux via OH $ -activated outward-rectified (GORK) K + channels (Demidchik et al, 2010). Thus, the strong increase in Glu levels found in the root apex (Table I) may be an additional factor exacerbating a stress-induced decrease in the cytosolic K + pool in this zone, leading to the activation of caspase-like enzymes and, finally, programmed cell death (Fig.…”
Section: Changes In Primary Metabolism Exacerbate Differential K + Rementioning
confidence: 85%
See 3 more Smart Citations
“…Plant GLRs were confirmed recently to be NSCC (Price et al, 2012;Forde, 2014). Therefore, activated by Glu, GLR may mediate stress-induced Ca 2+ uptake, with a consequent rise in cytosolic Ca 2+ , that in turn can activate the plasma membrane NADPH oxidase (Lecourieux et al, 2002), leading to elevated H 2 O 2 levels and a consequent formation of OH $ (as discussed above), leading to a massive K + efflux via OH $ -activated outward-rectified (GORK) K + channels (Demidchik et al, 2010). Thus, the strong increase in Glu levels found in the root apex (Table I) may be an additional factor exacerbating a stress-induced decrease in the cytosolic K + pool in this zone, leading to the activation of caspase-like enzymes and, finally, programmed cell death (Fig.…”
Section: Changes In Primary Metabolism Exacerbate Differential K + Rementioning
confidence: 85%
“…By interacting with transition metals such as either copper or iron, increased accumulation of hydrogen peroxide (H 2 O 2 ) may result in the formation of highly reactive hydroxyl radicals (OH $ ) in both the apoplast (Demidchik, 2015) and cytosol (Rodrigo-Moreno et al, 2013). Both H 2 O 2 and OH $ may cause a major perturbation in intracellular ionic homeostasis by activating a range of cation-permeable ion channels (Demidchik and Maathuis, 2007;Demidchik et al, 2010;Shabala and Pottosin, 2014). Thus, tissuespecific salinity stress sensitivity between the root apex and mature zones may be causally related to the patterns of OH $ production and/or sensitivity of membrane transporters to OH $ .…”
Section: Higher Sensitivity Of the Root Apex To Salinity May Be Relatmentioning
confidence: 99%
See 2 more Smart Citations
“…7 To deal with Fe-or Cu-induced toxicity, plants need to enhance antioxidant defenses; this phenomenon has been reported for a wide range of species such as radicals-activated K + channels are involved in programmed cell death in plant cells. 33 Recently, Lahoavist et al 36 showed that the hydroxyl-radical activated Ca 2+ and K + conductance in Arabidopsis is mediated by annexin1 at the mature and elongation zone levels. In all these studies, the hydroxyl radical generation occurred at the external side of the plasma membrane, and under non-physiological (1mM of the hydroxyl-radical generation mixture Cu/Asc) conditions.…”
Section: Transition Metalsmentioning
confidence: 99%